Corynebacterium diphtheriae endocarditis - de Campos, Fernando Peixoto Ferraz; Takayasu, Vilma; Deutsch, Hugo; Staniak, Henrique Lane; dos Santos, Silvia Regina (Autopsy and Case Reports, 2011)
The authors report the case of a 69-year-old man with an acute toxemic and febrile syndrome. Immediately after admission, the patient’s mental status rapidly deteriorated. A faint mitral systolic murmur was detected and splenomegaly wasobserved on ultrasound examination. Laboratory screening revealed azotemia, AST and ALT elevation, leukocytosis, thrombocytopenia, elevated erythrocyte sedimentation rate as well as C-reactive-protein. Urinalysis showed proteinuria,leukocyturia and hematuria. A transesophageal echocardiogram showed large vegetations attached to both mitral leaflets with mild regurgitation. Blood culture yielded slow-growing Gram-positive bacillus which was later identified as a nontoxigenic Corynebacterium diphtheriae sorovar gravis. The authors emphasize the importance of identifying any bacteria isolated in blood samples particularly when an infective endocarditis diagnosis is suspected and call attention to theincreasing number of reports related to this pathogen. Patient’s clinical outcome was favorable after a long period of antibiotic therapy.